Changing Patterns of Indian Trapping in the Canadian Subarctic - VanStone, James W. (ARCTIC, 1963)
Describes changes observed among Chipewyans at Snowdrift in southwestern Mackenzie District in 1960-1961, and considers their duplication and significance throughout the Subarctic. At Snowdrift, trapping has decreased in area, intensity, and popularity. Among the factors responsible are other sources of income (mainly government), establishment of a school, improved village housing, and fluctuations in fur prices. Trapping patterns in various other communities examined from the literature indicate a general decline in the western and, to a lesser extent, eastern Subarctic. Some factors however, especially lack of other job opportunities, tend to foster continued trapping.